Asthenopic symptoms prevalence in undergraduate students - Nunes,Flávio Marconiedson (2018)
Abstract Objective: To analyze the prevalence of asthenic symptoms in students of higher education and to assess their influence on academic performance and learning. Methods: Descriptive research with cross-sectional design through the application of the College of Optometrists Questionnaire in Vision Development Quality of Life (COVDL-QoL), in its cross-cultural and linguistic adaptation to the Portuguese language, to the students of a private college in the city of Montes Claros. Results: The questionnaire was answered by 132 university students. There was no significant discrepancy in the prevalence of asthenopia between genders and age. Symptoms of headache, poor memory and loss of objects predominated in women, while sleepiness during reading and poor management of time were predominant in males. Conclusion: A high prevalence rate of asthenic symptoms among university students and positive associations with sex and time of use of electronic equipment was identified.